Machining and Surface Characteristics of AISI 304L After Electric Discharge Machining for Copper and Graphite Electrodes in Different Dielectric Liquids - Anjum, S.; Shah, M.; Anjum, N. A.; Mehmood, S.; Anwar, W. (Engineering, Technology & Applied Science Research, 2017)
In Electric Discharge Machining (EDM), the thermal energy used for material erosion depends on the intensity of electric sparks, the thermal conductivities of electrode material and the dielectric liquid. In this paper, the effect of EDM on AISI 304L steel is studied using copper and graphite electrodes and distilled water and kerosene oil as dielectric liquids. Material Removal Rates (MRR), Tool Wear Rates (TWR) and surface conditions are calculated for four different combinations with the two electrode materials and the two dielectric liquids. These investigations are carried out at different pulse currents. Machined surfaces are evaluated by morphological studies, energy dispersive spectrographs (EDS) and white layer thickness using Scanning Electron Microscopy (SEM). It is found that a transfer of carbon takes place from the kerosene oil and the graphite electrodes into the machined surface which alters the metallurgical characteristics, depending on the electrical and thermal conductivities of the electrode material and the dielectric liquid.